Control of Chaotic Calcium Oscillations in Biological Cells - Quanbao Ji; Min Ye (Complexity)
The contribution of this present paper is to propose a method that combines a chemical Brusselator reaction-diffusion system with a biological cell system via gap junction for controlling and visualizing the frequency and magnitude of chaotic intracellular calcium oscillations in two cell types, including nonexcitable cells and the glial cells. This produces a wide variety of oscillatory behaviors similar to those reported in numerous biological experiments. We particularly show that in the majority of chaos cases, the reactor to cell coupling can induce the generation of regular calcium oscillations as the coupling strength is varied. Together with the proposed method of coupled models, the regularity of these chaotic oscillations enables us to gain better understanding and extensive insights into the overall coupling dynamics.